Railroads: Recent Books and Neglected Problems: A Correction - Burgess, Kenneth F.; Vanderblue, Homer B.; Ripley, William Z. (Quarterly Journal of Economics, 1926)
Kenneth F. Burgess, Homer B. Vanderblue; A Correction, The Quarterly Journal of Economics, Volume 40, Issue 2, 1 February 1926, Pages 346–347, https://doi.